341 Effects of Supplemental Betaine on Protein Deposition and Plasma Amino Acid Concentrations in Growing Steers with Modulated Methyl Group Status. (21st September 2022) - Grant, Madeline S; Marsh, Jessica M; Hazlewood, Kathryn J; Miesner, Matt D; Titgemeyer, Evan C
Abstract: Methyl group donors (e.g., methionine, betaine) may improve performance of growing beef cattle. Our objective was to evaluate effects of betaine supplementation on protein deposition and plasma amino acids in growing steers with altered methyl group status. Seven ruminally cannulated Holstein steers (189 kg) were used in a 6×6 Latin square design with 10-d periods. Factorial treatments were continuously infused abomasally and included 3 methyl group modulators [MGM; control; 15 g/d guanidinoacetic acid (GAA); or 16.8 g/d creatine] and 2 levels of betaine (0 or 5.7 g/d betaine). Supplemental GAA or creatine increases body creatine supply; however, GAA consumes methyl groups during creatine synthesis, whereas creatine spares methyl groups by reducing GAA synthesis. Steers received 3.5 kg/d (DM basis) of a corn-based diet. Total collection of urine and feces occurred on d 7 through 9 to measure N retention. Jugular blood was collected on d 10. No interactions between MGM or betaine were observed (P≥0.17). Betaine supplementation increased retained N (P=0.03), but did not affect urinary or fecal N excretion (P≥0.16). Betaine increased plasma Met (P=0.03) and cystine (P=0.04) and tended to decrease plasma Lys (P=0.10). Nitrogen retention was not affected by MGM (P=0.63). Creatine increased urinary N (P=0.04), and GAA tended to increase urinary N (P=0.08). Creatine increased fecal N excretion relative to control (P=0.02); GAA also increased fecal N relative to control (P< 0.01). Plasma Met was not affected by MGM (P=0.41). Plasma cystine was decreased by creatine relative to control (P=0.01), but was not affected by GAA relative to control (P=0.26). Plasma Lys was decreased by GAA (P< 0.01) and creatine (P=0.05) relative to control. Supplemental betaine improved protein deposition in growing steers and altering methyl group status affected plasma amino acid concentrations.